Heteronuclear NMR Spectroscopy as Surface‐Selective Technique: A Unique Look at the Hydroxyl Groups of γ‐Alumina. Issue 14 (13th March 2014) - Taoufik, Mostafa; Szeto, Kai C.; Merle, Nicolas; Rosal, Iker Del; Maron, Laurent; Trébosc, Julien; Tricot, Grégory; Gauvin, Régis M.; Delevoye, Laurent
Abstract Invited for the cover of this issue are the groups of Régis M. Gauvin at the Université Lille Nord de France, Laurent Maron from the Université de Toulouse, and Mostafa Taoufik from the Université Lyon 1. The image depicts data on the topology of the surface hydroxyl groups of γ‐alumina as a postcard. Read the full text of the article at 10.1002/chem.2013004883.